2014
DOI: 10.1128/aac.03858-14
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Inhibitors of the Pseudaminic Acid Biosynthetic Pathway: Targeting Motility as a Key Bacterial Virulence Factor

Abstract: Helicobacter pylori is motile by means of polar flagella, and this motility has been shown to play a critical role in pathogenicity. The major structural flagellin proteins have been shown to be glycosylated with the nonulosonate sugar, pseudaminic acid (Pse). This glycan is unique to microorganisms, and the process of flagellin glycosylation is required for H. pylori flagellar assembly and consequent motility. As such, the Pse biosynthetic pathway offers considerable potential as an antivirulence drug target,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 46 publications
(55 reference statements)
5
44
0
Order By: Relevance
“…53 Closely related to the work in this paper, the Sulea and Logan research groups have reported an inhibitor that targets the pseudaminic acid biosynthetic pathway found in H. pylori and C. jejuni . 54 The “sialic-acid like” nonulosonate sugar product is required for the glycosylation of structural flagellin proteins and exposure to inhibitors attenuated flagellin production at concentrations of ≥100 μM. The flagella are required for persistent infections of H. pylori and this work demonstrates the link between bacterial glycosylation and pathogenicity using chemical tools (as opposed to genetic modification).…”
Section: Discussionmentioning
confidence: 81%
“…53 Closely related to the work in this paper, the Sulea and Logan research groups have reported an inhibitor that targets the pseudaminic acid biosynthetic pathway found in H. pylori and C. jejuni . 54 The “sialic-acid like” nonulosonate sugar product is required for the glycosylation of structural flagellin proteins and exposure to inhibitors attenuated flagellin production at concentrations of ≥100 μM. The flagella are required for persistent infections of H. pylori and this work demonstrates the link between bacterial glycosylation and pathogenicity using chemical tools (as opposed to genetic modification).…”
Section: Discussionmentioning
confidence: 81%
“…Currently, carbohydrate-based therapies and diagnostics in cancer research and infectious disease have received considerable attention. Menard et al identified three inhibitors of the pseudaminic acid biosynthetic enzymes which show activity in inhibiting the flagellin proteins on the C. jejuni cell surface, by bacterial cell-based assays (Menard et al, 2014). In this study, we found the prevalence of the jhp0106 gene among 95 clinical isolates of H. pylori in Taiwan was 100%.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori flagellin proteins are synthesized, then post-translationally modified intracellularly by glycosylation with a nine carbon pseudaminic acid sugar derivative that resembles sialic acid (Schirm et al, 2003; Logan, 2006). The enzymes of the pseudaminic acid biosynthetic pathway in H. pylori , in order, are PseB, PseC, PseH, PseG, and PseI (Schirm et al, 2003; Menard et al, 2014), and the glycosylation process is essential for assembly of functional flagellar filaments and consequent bacterial motility (Schoenhofen et al, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…In pathogens such as Campylobacter jejuni and Helicobacter pylori, flagellin glycosylation is required for flagellum assembly, bacterial motility, and colonization ability, and therefore 1 9 associated with virulence 8 . Flagellin glycosylation therefore offers potential as an antivirulence target, and hence small molecule inhibitors of nonulosonic acid biosynthesis 91 Albeit these systems are available for studying putative legionaminic acid and pseudaminic acid transferases, our demonstration of donor substrate promiscuity (especially with respect to KDO transferase activity) has the implication that Maf proteins may be easily subjected to high-throughput screening for small molecule inhibitors or to other biochemical characterization using a common lab strain of E. coli.…”
Section: Discussionmentioning
confidence: 99%